Desarrollo postembrionario de Ronderosia bergi (Orthoptera: Acrididae: Melanoplinae) bajo condiciones controladas - Mariottini, Yanina (2006)
First generation cohorts obtained in the laboratory from field collected (southeast of San Luis province) individuals of the grasshopper Ronderosia bergi (Stål), were used to measure some developmental parameters of the species under controlled conditions (30°C, 40% RH, 14 hs. L: 10 hs. D). The total duration of the postembryonic development was 213 days, of which thirty were devoted to the five instars of nymphal development. The mean number of eggs per eggpod was 16.8, and sexual maturity was reached 4-5 days after the last molt. Differences with data coming from other studies may be due to the different conditions used or the high intraspecific variability of R. bergi.